Antipsychotic Drugs and Liver Injury. Issue 1 (25th July 2018) - Lv, Qinyu; Yi, Zhenghui
Abstract : In October 2015, the drug-induced liver diseases group of the Chinese Society of Hepatology drafted and published the first Diagnosis and Treatment Guidelines on Drug-induced Liver Injury in China, giving suggestions on the diagnosis and treatment of drug-induced liver injury (DILI). As a psychiatrist, I have found that in clinical practice both typical and new antipsychotic drugs can induce liver injury to varying degrees. Therefore, it is necessary to quickly and accurately determine the cause of liver injury and the type and severity of injury and establish a solution. This article reviewed relevant literature including the common pathogenesis and clinical manifestations of drug-induced liver injury caused by antipsychotic drugs, laboratory tests, diagnostic criteria and classification, and clinical management strategies. This paper also includes a summary and a perspective on liver injury caused by antipsychotic drugs.